QUALITY ASSESSMENT OF EDUCATIONAL CONTENT IN GRADUATING DEPARTMENTS USING INFORMATION-EXTREME INTELLECTUAL TECHNOLOGY OF DATA ANALYSIS - А. С. Довбиш; Є. С. Кулік; З. В. Козлов; А. С. Осадчий (Радіоелектронні і комп'ютерні системи, 2019)
We consider information synthesis of able to learn informational and analytical system for assessing adaptation of graduating department educational content to the requirements of the labor market. As part of the informationextreme intellectual technology, which is based on maximizing the capacity of information in the process of learning, algorithm of geometrical parameters optimization of class recognition containers renewable in the radial basis of attribute space is offered. Forming input mathematical description of information-analytical system was carried out of a survey of employers and graduates with experience in base speciality for compliance with the current requirements of content modules of ten disciplines with professional training.